A compact and simple method of achieving differential transgene expression by exploiting translational readthrough - James E Sillibourne; Giulia Agliardi; Matteo Righi; Katerina Smetanova; Grant Rowley; Simon Speller; Abigail Dolor; Katarina Lamb; Christopher Allen; Rajeev Karattil; Farhaan Parekh; Frederick Arce Vargas; et al. (BioTechniques)
The development of multicistronic vectors enabling differential transgene expression is a goal of gene therapy and poses a significant engineering challenge. Current approaches rely on the insertion of long regulatory sequences that occupy valuable space in vectors, which have a finite and limited packaging capacity. Here we describe a simple method of achieving differential transgene expression by inserting stop codons and translational readthrough motifs (TRMs) to suppress stop codon termination. TRMs reduced downstream transgene expression ∼sixfold to ∼140-fold, depending on the combination of stop codon and TRM used. We show that a TRM can facilitate the controlled secretion of the highly potent cytokine IL-12 at therapeutically beneficial levels in an aggressive immunocompetent mouse melanoma model to prevent tumor growth. Given their compact size (6 bp) and ease of introduction, we envisage that TRMs will be widely adopted in recombinant DNA engineering to facilitate differential transgene expression.